THE PRINCIPLE OF PSYCHOLOGICAL INDEPENDENCE IN HUMANISTIC COUNSELLING BASED ON HADITH - Danang Firdaus; Ahmad Musyafiq (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2025)
This study is motivated by the need to address an empirical void concerning the integration of hadith-derived values into the cultivation of psychological autonomy within humanistic counselling, particularly to respond to maladaptive dependencies such as drug abuse. The research adopts a qualitative literature-based design. The corpus of authenticated hadith was hermeneutically interpreted and triangulated with contemporary counselling scholarship to derive operational indicators of autonomy. Analysis revealed two primary mechanisms: the construction of religious meaning that bolsters intrinsic motivation, and the activation of emotion-regulation techniques through ritual practices, such as dhikr (asking for forgiveness) and patience training, as adaptive coping strategies. Based on these findings, the study formulates three operational indicators, affective regulation, authentic decision-making, and moral responsibility, that can be translated into psychometric items and intervention modules. In conclusion, integrating hadith offers a values-grounded framework and practical techniques that enrich humanistic counselling while remaining culturally resonant. Recommendations address researchers in developing and validating measurement instruments; clinicians in adapting intervention modules with cultural competence; and policymakers in supporting controlled trials of evidence-based, culturally tailored interventions. The study also emphasises content validation by hadith scholars and counselling experts, rigorous psychometric testing, pilot-controlled evaluations, and standardised training for Muslim counsellors to ensure ethical implementation and ongoing monitoring.